Shane ebook - Schaefer, Jack (2017)
In this true Western classic Jack Schaefer tells the story of a mysterious stranger who finds himself in the Wyoming Territory joining local homesteaders in their fight to keep their land and avoid the intimidating tactics of cattle driver Luke Fletcher. While trying to leave his gunslinging days behind him, the mysterious stranger, Shane, is tested by Fletcher and his men. In Shane, Schaefer executes a perfect Western narrative while exploring the overarching themes of virtue, the human condition, and a man's search for self. | In this true Western classic Jack Schaefer tells the story of a mysterious stranger who finds himself in the Wyoming Territory joining local homesteaders in their fight to keep their land and avoid the intimidating tactics of cattle driver Luke Fletcher. While trying to leave his gunslinging days behind him, the mysterious stranger, Shane, is tested by Fletcher and his men. In Shane, Schaefer executes a perfect Western narrative while exploring the overarching themes of virtue, the human condition, and a man's search for self.